Metabolic Optimization by Enzyme-Enzyme and Enzyme-Cytoskeleton Associations - Araiza-Olivera, Daniela; Uribe-Carvajal, Salvador; Chiquete-Félix, Natalia; Rosas-Lemus, Mónica; Granados, Gisela Ruíz-; Sampedro, José G.; Mújica, Adela; Peña, Antonio (IntechOpen, 2012)
None